The Process Of Capacity Building In The Bureau of The Procurement of Goods and Service In Banten Province During The COVID-19 Pandemic - Soerjo Soebiandono; Sinta Ningrum; Heru Nurasa; Ramadhan Pancasilawan (Aliansi, 2022)
The era of bureaucratic reform is marked by the government's efforts to improve public services that are efficient, effective, transparent, and accountable. Quality public services as a process of governance can have implications for achieving government goals (Hayat, 2020). As a newly formed organization, the Bureau of Procurement of Goods and Services of Banten Province experienced various obstacles in public services. This is also found in various studies of barriers to public services caused by weak human resources and limited supporting infrastructure, especially during the COVID-19 pandemic. Good governance will be achieved if efforts to increase the capacity and capability of local governments are carried out in a structured and planned manner through capacity building. Therefore, an effort is needed to improve innovation through capacity building. This study aims to analyze how the capacity building process in the procurement bureau of goods and services in Banten Province is expected to be the basis for policy making in development in Banten Province, especially the development of public services with the characteristics of Banten Province. This study uses qualitative research methods to analyze comprehensively and in-depth the process of capacity building in the implementation of the Procurement of Goods and Services.